Antibacterial Activity and Salinity Tolerance of Endophytic Bacteria Isolated from Marine Macroalgae (Biosaintifika: Journal of Biology & Biology Education, 2026)
Marine organisms, especially macroalgae, are unique microhabitats for endophytic bacteria that have the potential to provide unique microhabitats for endophytic bacteria that can produce bioactive compounds with antimicrobial activity.  However, the exploration of endophytic bacteria from marine macroalgae, especially those directly associated with host tissues, remains relatively limited. This study aims to isolate endophytic bacteria from various macroalgae and explore the antibacterial potential and salinity resistance of these endophytic isolates. This study aims to identify the potential isolates that produce antibacterial compounds at the molecular level. The antibacterial activity was qualitatively evaluated using the Kirby–Bauer disk diffusion method. The salinity tolerance of the bacterial isolates was assessed by growing them on media with varying NaCl concentrations. Molecular identification of the isolates was performed through 16S rRNA gene amplification and sequence analysis. The results showed that isolate H3 had the highest antibacterial activity against Bacillus subtillis and Staphylococcus aureus, with inhibition zones of 28.9 + 2.3 mm and 26.2 + 4.36 mm, respectively. Isolate R1A showed the highest inhibitory activity on S. aureus and Escherichia coli, with inhibition zones of 25 + 1.08 mm and 35 + 2.9 mm. Salinity resistance test results showed that isolate R1A was able to grow well at a 10% (w/v) NaCl concentration. Molecular identification results with 16S rRNA gene analysis showed that isolate H3 has similarities with the species Lysinibacillus fusiformis, isolate R1A has similarities with Bacillus mojavensis, and R2C has similarities with Bacillus stercosis. This study suggests that endophytic bacteria from macroalgae represent promising and sustainable sources of novel antibacterial agents for pathogen control in high-salinity aquaculture systems. This study aligns with SDG 3 and SDG 14 by supporting human health initiatives and the sustainable utilization of marine biodiversity.